PENERAPAN MODEL PEMBELAJARAN DISCOPERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA KELAS X SMA NEGERI 1 BATU HAMPAR TAHUN PELAJARAN 2015/2016 - Liana, Eka; ', Arnentis; Fauziah, Yuslim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is class room action research which is aimed to improve biology studying achievement by implementing guided Discopery Learning model in class X3 SMAN 1 Batu Hampar in Academic Year 2015/2016. This research was conducted in Maret-April The subject of this research was student of class X3 of SMA 1 Batu Hampar. The number of students was 31 students (15 boys and 16 girls). The Parameter was students passing individually,student activities and teachers activities. Students comprehension ability in cycle 1 was 77.3 % (pass) increased became 88.05 (good). The students passing studying in cycle 1 was 76.90 (pass) increased in cycle 2 became 80.90 (good). Acverage of student activities in cycle I was 83.73 % (pass) incresed in clycle 2 became 95.7% (very good). Average of teachers activities in cycle 1 was 75 % (pass) increased in cycle 2 became100% (very good). From the result of this research it can be concluded that the implementation of guided Discopery Learning model can improve students biology studying achievements in class X3 SMA 1 Batu Hampar in Academic Year 2015/2016.Keywords: Discopery Learning , Biology studying achiement